Plerixafor Salvage Is Safe and Effective in Hard-to-Mobilize Patients Undergoing Chemotherapy and Filgrastim-Based Peripheral Blood Progenitor Cell Mobilization. (10th April 2012) - Awan, Farrukh T.; Kochuparambil, S. Thomas; DeRemer, David; Cumpston, Aaron; Craig, Michael; Jillella, Anand; Hamadani, Mehdi
Abstract : The combination of filgrastim (G-CSF) and plerixafor is currently approved for mobilizing peripheral blood progenitor cells in patients with non-Hodgkin lymphoma and multiple myeloma undergoing autologous peripheral blood hematopoietic cell transplantation. However, chemotherapy and G-CSF-based mobilization remains a widely used strategy for peripheral blood progenitor cell collection. In this paper we describe our experience from two North American transplant centers in a series of patients who received salvage plerixafor while failing chemotherapy and G-CSF mobilization. Patients received a median of two doses of plerixafor salvage upon failure to mobilize adequate number of peripheral blood progenitor cells at neutrophil recovery. The use of plerixafor was associated with a 2.4-fold increase in peripheral blood CD34+ cell count and 3.9-fold increase in total CD34+ cell yield. All patients were able to collect ≥2 × 10 6 CD34+ cells/kg with this approach. These results were more pronounced in patients with a higher CD34+ cell count at the time of the first plerixafor dose. Interestingly, peripheral blood white blood cell count was not shown to correlate with a response to plerixafor. Our results provide safety and efficacy data for the use of plerixafor in patients who are destined to fail chemomobilization.